Tieto- ja viestintätekniikka eri oppijatyyppien tukena vieraan kielen opinnoissa - Ohinen-Salvén, Maarit (2013)
This study focuses on how learners with different learning styles can best use and profit from the different possibilities offered by e-learning in their second language acquisition. The study also discusses the alternatives to integrate the traditional learning in the classroom with distance learning using the solutions offered by e-learning. Aspects relevant to theories on second language acquisition, e-learning and different learning styles are extensively discussed. The study is both an action research and a case study research. The data measuring the students’ learning styles and experiences of using e-learning in their second language studies were gathered at HAAGA-HELIA University of Applied Sciences using structured and free text questionnaires. The target group consisted of ICT-students. The learners’ responses were analyzed qualitatively. As a result of this study, new information was gathered about what kind of opinions and objectives the learners with different learning styles have and how they experience the use of e-learning in their second language acquisition. The study concludes that it is essential to encourage language teachers to see the importance of differentiating their tuition and offering as diverse solutions as possible in order to provide the learners with an opportunity to choose the way of studying and learning which suits them best.